Plain language in legal drafting: challenges and opportunities in Indonesian regulatory reform - Muhamamad Faiz Ramadhan (Indonesian Journal of Linguistics and Legal Discourse, 2026)
Background: The complexity of Indonesian legal drafting has long undermined public accessibility, as most statutes and regulations remain unreadable for the majority of citizens. Objective: The purpose of this research is to examine the challenges and opportunities of implementing plain language in Indonesian regulatory reform. Method: Using a mixed-method design, this study integrates readability analysis, syntactic complexity assessment, and discourse analysis on a corpus of statutory and regulatory texts. Results: The results show that Indonesian legal documents record very low readability scores, requiring graduate-level comprehension, and exhibit entrenched structural obstacles such as long sentences, passive constructions, and nominalizations. Discourse analysis further reveals that legal texts reproduce authority through formulaic expressions and intertextual references, limiting inclusivity and citizen engagement. However, plain language guidelines introduced by national agencies demonstrate that reform is feasible, offering pathways toward more accessible and participatory lawmaking. Implication: The implication of this study is that plain language reform is not merely a linguistic choice but a necessary institutional transformation for democratic governance. Novelty: This study highlights how entrenched linguistic and discursive conventions in Indonesian legal drafting limit public accessibility while demonstrating the transformative potential of plain language for more inclusive and participatory governance.